Analytical Method to Determine Transportation Service Gaps for Transportation Disadvantaged Populations. Issue 8 (December 2018) - Bejleri, Ilir; Noh, Soowoong; Gu, Zongni; Steiner, Ruth L.; Winter, Sandra M.
Transportation disadvantaged (TD) populations, which include elderly people, people with disabilities, and people who do not own a vehicle, face mobility challenges because alternative transportation services are limited. To identify specific transportation service gaps for TD populations, an assessment of both transportation demand and transportation accessibility is necessary. Previous studies have focused on a single aspect of transportation accessibility or on studying geographic transportation gaps at the state or county level. This study develops a methodology aimed at identifying TD populations with major gaps in alternative transportation services. Using spatial overlays and network analysis, we develop a model for calculating transportation supply through a comprehensive transportation accessibility measure that considers relevant trip destinations and three alternative transportation services: public transportation, on-demand services, and taxi services. Gaps in service are identified by overlaying the TD population demand volume with transportation accessibility. The resulting supply–demand matrix highlights transportation deficient areas and populations, based on overlays of high demand and low supply. We apply this methodology to Alachua County, Florida. Results expose areas of deficiency, some in unexpected places. The findings highlight the need to assess alternative transportation for TD populations, to determine gaps to be addressed to improve TD populations' mobility and reduce personal auto trips and related traffic injuries. This method can guide policy makers in fostering equitable transportation provision across users.